Stability and change of postchemotherapy symptoms in relation to optimism and subjective stress: A prospective study of breast cancer survivors. Issue 10 (21st August 2019) - Cohen, Miri; Levkovich, Inbar; Pollack, Shimon; Fried, Georgeta
Abstract: Objectives: Inconsistent findings were reported about the course of postchemotherapy symptoms; specifically, the effect of changes in optimism and perception of subjective stress on the evolution of symptoms remains understudied. This prospective study aimed (a) to examine the course of postchemotherapy symptoms of emotional distress, fatigue, and cognitive difficulties among breast cancer survivors and (2) to assess the effect of changes in optimism and subjective stress on the trajectory of these symptoms. Methods: Ninety‐eight breast cancer survivors, diagnosed at stages I to III, aged 30 to 74, recruited consecutively (response rate 84.7%) completed fatigue, emotional distress, self‐reported cognitive difficulties, optimism, and subjective stress questionnaires at three points in time: upon enrollment (1‐6 months after completing treatment, Time 1) posttreatment, 6 months (Time 2), and 12 months (Time 3). A linear mixed‐effects model was used to analyze the data. Results: Emotional distress decreased between time‐points, level of cognitive difficulties remained stable, and a marginal decrease in fatigue was evident. Optimism or subjective stress predicted changes in each of the symptoms ( P <.01), except for the effect of optimism on cognitive difficulties ( P =.06). The interactions between time and optimism and between time and subjective stress were only significant regarding their effect on emotional distress ( P <.05), showing that the strongest effect of these variables was at Time 2. Conclusion: The course of postchemotherapy symptoms shows patterns of stability and change over a 1‐year period. Optimism and subjective perceptions of stress were shown to affect the decrease of symptoms. Therefore, these two factors should be specifically targeted in psycho‐social interventions.